Pengembangan Kurikulum Program Studi Hukum Keluarga Islam Berbasis Kebutuhan Masyarakat untuk Pencegahan Perkawinan Anak - Bin Ridwan, Rifanto; Husein, Muhammad (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2025)
This study aims to identify the factors contributing to child marriage in Rejang Lebong and Kepahiang Regencies, develop a community needs-based curriculum model for the Islamic Family Law (HKI) Study Program, and provide recommendations for curriculum implementation to enhance graduates' competencies as agents of social change. The research employs a qualitative approach with a descriptive-analytical method, involving in-depth interviews, participatory observation, and document analysis. Informants include heads of Religious Affairs Offices (KUA), community leaders, child marriage couples, and lecturers from the HKI Study Program. The findings reveal that the primary factors driving child marriage include premarital pregnancy, economic pressures, low educational attainment, social norms, and the influence of modern technology. Based on these findings, a curriculum model was developed incorporating new courses such as family law counseling methods, conflict management, and mini-field research to directly address community needs. The curriculum is also designed to integrate modern technology into learning to support 21st-century competencies. The study concludes that developing a community needs-based curriculum has the potential to reduce child marriage rates, increase legal awareness, and empower HKI graduates as solutions to social problems. With cross-sector collaboration and continuous evaluation, this curriculum can serve as an applicable model for other educational institutions.